L’élargissement de l’OTAN - Philippe Boulanger (EchoGéo)
Summary: the summit of Bucharest (in April 2-4th, 2008) joins in the continuity of a process engaged after the fall of the USSR in 1991. This process tends to widen the zone NATO as its sphere of influence eastward, by proceeding either to news integration, or in new partnerships. This process of release is not either without raising of problems in the returning power of Russia. What are the stakes and the risks of the summit of Bucharest?